Synthesis and Characterization of Reduced Graphene Using Vitamin C for Conductive Electrode Applications - Zeng Feihu; SyYi Sim; Wang Zhiwen; Lai Mingrui (Majlesi Journal of Electrical Engineering)
In this study, reduced graphene oxide (rGO) was synthesized by reducing graphene oxide (GO) using Vitamin C (VC) as a reducing agent, to create a conductive electrode material. The structural and property effects of VC/GO mass ratios, reaction temperature and time on rGO were investigated in detail. Structural characterization and conductivity assessments of both GO and rGO were conducted using powder X-ray diffraction (XRD), Fourier-transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), Brunauer-Emmett-Teller (BET) surface area analysis, and a four-probe conductivity tester. The results showed that VC as a reducing agent effectively reduces the functional groups on the GO surface, forming C=C bonds, while also increasing the d-spacing of rGO. The increase of reaction temperature promotes the ionization and decomposition of VC, thereby improving the reaction efficiency. The synthesized rGO exhibited a porous network with an irregular structure formed by interconnected, wrinkled nanosheets. Optimal conditions were observed when the VC/GO mass ratio was 1:1, the reaction temperature was 100 °C, and the reaction time was 3 hours. Under these conditions, the synthesized rGO material achieved a resistivity of 1.82 Ω·cm and a resistance value of 2.75 Ω, positioning it as an excellent electrode material.